EBV & HHV8 and HIV in B cell non Hodgkin lymphoma in Kampala, Uganda - Tumwine, Lynnette K.; Orem, Jackson; Kerchan, Patrick; Byarugaba, Wilson; Pileri, Stefano A. (Uganda Infectious Agents and Cancer, 2010)
B cell non Hodgkin lymphomas account for the majority of lymphomas in Uganda. The commonest is endemic Burkitt lymphoma, followed by diffuse large-B-cell lymphoma (DLBCL). There has been an increase in incidence of malignant lymphoma since the onset of the HIV/AIDS pandemic. However, the possible linkages of HHV8 and EBV to the condition of impaired immunity present in AIDS are still not yet very clearly understood.
Keywords: EBV; HHV8; HIV; B cell non Hodgkin lymphoma; Uganda